SISTEM PEMERINTAHAN KESULTANAN LANGKAT - Rizka Dwi Kurnia (Journal Analytica Islamica, 2015)
Langkat Sultanate is one of the Malay Kingdom in the region of the East Coast of Sumatra Island. This kingdom comes with a strong Islamic style, reflected in the culture and art relics of Islamic architecture such as mosques and madrasas. Besides, the Sultanate langkat is the most prosperous kingdom in comparison with other kingdoms in East Sumatra. Langkat Sultanate also has a very good system of government as well as structured.